Kecerdasan Majemuk dalam Perspektif Psikologi Pendidikan Islam - Sani, Mutiara; Rokhimah, Siti (TSAQOFAH, 2026)
Islamic education aims to develop the full range of human potential holistically in order to form insān kāmil, characterized by faith, knowledge, and noble character; however, educational practice in the field still tends to emphasize intellectual intelligence as the primary indicator of learning success and therefore has not fully accommodated the diversity of students’ potentials. This article aimed to analyze the concept of multiple intelligences from the perspective of Islamic educational psychology through a library research approach. Data were drawn from relevant primary and secondary literature and analyzed using content analysis techniques. The findings indicate that the concept of multiple intelligences is conceptually aligned with the Islamic view of fitrah as multidimensional human nature. Integrating multiple intelligences into Islamic educational psychology contributes to strengthening a holistic and humanistic educational paradigm oriented toward developing students’ intellectual, emotional, social, and spiritual potentials. This article is expected to serve as a conceptual reference for advancing the theory and practice of Islamic Religious Education that is more oriented toward the holistic humanization of learners.